Advancing Malaysian youth development: promoting Anugerah Remaja Perdana Rakan Muda (The international award by the Duke of Edinburgh - Zeh Kang, Beh; Yaccob, Yasmin; Tobias, Mariam (Human Resource Management Academic Research Society, 2024)
The Anugerah Remaja Perdana Rakan Muda program, also known as the Duke of Edinburgh’s International Award (hereinafter referred to as “The Award”), is a global initiative designed to engage young people in purposeful activities that promote personal growth, leadership, and community involvement. By focusing on an experiential learning model, the program aims to complement formal education, equipping participants with essential life skills such as teamwork, problem-solving, and resilience. This article examines The Award’s structure, which is divided into three levels—Bronze, Silver, and Gold—each comprising four sections: Service, Skills, Physical Recreation, and Adventurous Journey. Operating in over 140 countries and territories, The Award’s non-formal educational framework has been lauded for its comprehensive approach to youth development. Participants consistently report gains in confidence, improved interpersonal skills, and a greater sense of responsibility, ultimately leading to meaningful contributions within their communities. The significance of The Award will be explored in fostering holistic youth development, with a focus on its role in shaping future leaders, encouraging civic engagement, and connecting Malaysian youth to a broader international network. Through case studies and participant testimonials, the article will demonstrate how The Award empowers young people to realize their full potential and make a positive impact in both local and global contexts.